2019
DOI: 10.1038/s41598-019-53422-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of CPV2c introgression into Croatia and novel insights into phylogeny and cell tropism

Abstract: Canine parvovirus type 2 (CPV2) emerged for the first time in 1978 and evolved into two antigenic variants CPV2a and CPV2b and the third new antigenic variant CPV2c reported in 2000 in Italy. During 2014 unexplained outbreaks of gastroenteritis were observed in kennels where an extensive vaccination program was ongoing and where vaccinated animals showed pathologic lesions consistent with typical parvovirosis. The aim of this study was to investigate whether CPV2 could have played a role in the emergence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
(80 reference statements)
1
3
0
Order By: Relevance
“…Interestingly, even in a few cases in which CPV-2 was not detected, histopathological changes suggested it as the probable cause of the disease and death. The lesions observed in cases of parvovirosis are well defined and characterized by necrotizing enteritis with squamous metaplasia, necrosis and fusion of crypts, villous atrophy, epithelial syncytia in crypts and Peyer's patch necrosis (DE OLIVEIRA et al, 2018;GODDARD & LEISEWITZ, 2010;MOON et al, 2008;NOVOSEL et al, 2019), similar to those observed in most cases of enteritis associated with CPV-2 reported here (Figure 1A). Other viral agents commonly related to enteric disease in dogs promote different histopathology lesions.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, even in a few cases in which CPV-2 was not detected, histopathological changes suggested it as the probable cause of the disease and death. The lesions observed in cases of parvovirosis are well defined and characterized by necrotizing enteritis with squamous metaplasia, necrosis and fusion of crypts, villous atrophy, epithelial syncytia in crypts and Peyer's patch necrosis (DE OLIVEIRA et al, 2018;GODDARD & LEISEWITZ, 2010;MOON et al, 2008;NOVOSEL et al, 2019), similar to those observed in most cases of enteritis associated with CPV-2 reported here (Figure 1A). Other viral agents commonly related to enteric disease in dogs promote different histopathology lesions.…”
Section: Discussionsupporting
confidence: 78%
“…There were 22 nt (6 aa) differences identified in the partial, 1589 nt-long VP2 sequences between the study strain of FR1/CPV2-2021-HUN and Canigen, or Primodog CPV-2b vaccine strains, respectively (data not shown) suggesting that the identified field strain is most likely not a vaccine revertant mutant. Based on the continuous spreading of “Asian-origin” CPV-2 strains in nearby countries like Italy and Romania (Mira et al 2019 ; Novosel et al 2019 ; Balboni et al 2021 ) the appearance of an “Asian-origin” CPV-2 in Hungary is not unexpected, although to our current knowledge the fixed non-synonymous E426D mutation in VP2 in a field strain of this lineage is quite unusual. Based on previous phylogenetic analyses of CPV-2 VP2 sequences similar mutations affecting this site (VP2 426 ) – and therefore causing a change of the antigenic variant type – are rare but not unprecedented (Voorhees et al 2019 ).…”
Section: Resultsmentioning
confidence: 83%
“…Different variants of CPV-2 are presented worldwide with variable geographic distribution and abundance (Miranda and Thompson, 2016 ). Nowadays the rapid spread of recently emerged “Asian-origin” CPV-2c strains with characteristic aa mutations of NS1 ( 60 V , 544F , 545 V , 630P); NS2 ( 60 V , 151 N , 152 V) and VP2 ( 5G , 267Y , 297A , 324I and 370R ) are causing serious concerns in Asia and Europe as well (Mira et al 2019 ; Novosel et al 2019 ; Balboni et al 2021 ; Chen et al 2021 ). There are multiple types of commercially available and widely used vaccines against CPV-2, although still several CPV-2 infections-related HGE cases have been documented among vaccinated dogs (Decaro et al 2008 ; Qi et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A standard curve was generated using 10 1 to 10 9 copies per reaction of CBuV plasmid DNA constructed by cloning the 98 bp VP2 fragment of strain ITA/2011/297-15 (Martella et al, 2018) into pCR 2.1 vector of TA Cloning Kit (Invitrogen, Ltd.). All faecal samples were also tested for the presence of CPV-2, canine coronavirus (CCoV), canine kobuvirus (CaKoV) and norovirus (NoV) by qualitative PCR and reverse transcription (RT)-PCR (Buonavoglia et al, 2001;Di Martino, Di Felice, Ceci, Di Profio, & Marsilio, 2013;Pratelli, Tempesta, Greco, Martella, & Buonavoglia, 1999;Vennema, de Bruin, & Koopmans, 2002).…”
Section: Molecular Screeningmentioning
confidence: 99%